Tolerance and accumulation characteristics of Brassica chinensis L. under the interactive treatments of lanthanum, cerium, and fluorine in soil - Ying Jiang; Daixi Zhang; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Lichao Nengzi (BMC Plant Biology)
Abstract The extensive mining of bastnasite (CeFCO3) has caused severe pollution of lanthanum (La), cerium (Ce), and fluorine (F) in the surrounding farmland soil, threatening the safety of the soil-plant system. However, the stress effects of the interaction among these three elements on the tolerance and accumulation traits of Brassica chinensis L. (B. chinensis) are unclear. In this study, the interaction mechanisms of these three pollutants regulating the growth characteristics, antioxidant capacity, and accumulation characteristics of B. chinensis was explored using pot experiments of La-Ce (LC), Ce-F (CF), La-F (LF), and La-Ce-F (LCF) interactions. The LC interaction pollution treatments at the element concentrations higher than those of LC3 showed significant impact (P < 0.05) on the plant growth. The order of tolerance in B. chinensis under four interaction treatments was La-F > Ce-F > La-Ce-F > La-Ce, which was supported by the integrated biomarker response (IBR) analysis. The synergistic effect of La and Ce in La-Ce experiment promoted these two elements in the plants, whereas the presence of F in CF, LF, and LCF combined pollution treatments inhibited the absorption of La and Ce. Moreover, under the interaction among three elements, the synergistic effect of La and Ce in LC treatment enhanced the biotranslocation factor (BTF) of both elements, reaching the highest levels of 0.36 and 0.40, respectively. The addition of F in CF (BTF of 0.3 and 0.15, respectively), LF (BTF of 0.25 and 0.15, respectively), and LCF (BTF of 0.21, 0.24, and 0.15, respectively) treatments reduced the BTF of La and Ce in the plants due to the formation of insoluble precipitates between F with La or Ce. In conclusion, the interaction between La and Ce could reduce the tolerance of B. chinensis, while the presence of F could enhance the plant resistance to both La and Ce.